ChemInform Abstract: A Direct Approach to β‐Keto Sulfones via AgNO3/K2S2O8 Catalyzed Aerobic Oxysulfonylation of Alkenes in Aqueous Medium. Issue 4 (January 2015) - Singh, Atul K.; Chawla, Ruchi; Yadav, Lal Dhar S.
Abstract The one‐pot radical route to β‐ketosulfones involves oxysulfonylation of alkenes with air and inexpensive sodium arenesulfinate salts under mild reaction conditions.